2011
DOI: 10.1007/s11223-011-9321-x
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation structure and impact toughness of reactor pressure vessel steel 15Kh2NMFA upon ultrasonic treatment

Abstract: A. V. Mats, V. M. Netesov, UDC 621.789 and V. I. Sokolenko 1The paper addresses the influence of high-temperature ultrasonic treatment on the structure and impact toughness of steel 15Kh2NMFA. The observed increase of impact toughness and decrease of ductile-brittle transition temperature for the steel upon ultrasonic treatment of various durations are due to the formation of a uniform defect structure. Introduction.A study of the influence of ultrasound treatment on metals and alloys, which causes no form cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…By reducing the mean grain size of a Mg-3Al-Zn alloy to less than 3 µm, Liao et al [7] reported that the impact toughness is greatly improved due to enhancement of the dynamic strength and dynamic plastic deformation ability. It was reported by Mats et al [9] that the increase of the impact toughness for the steel 15Kh2NMFA upon high-temperature ultrasonic treatment of various durations is due to the formation of a uniform defect structure. For the LSP processing technology, the mechanical properties of the hardened layer are not uniform [1,2,[10][11][12].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…By reducing the mean grain size of a Mg-3Al-Zn alloy to less than 3 µm, Liao et al [7] reported that the impact toughness is greatly improved due to enhancement of the dynamic strength and dynamic plastic deformation ability. It was reported by Mats et al [9] that the increase of the impact toughness for the steel 15Kh2NMFA upon high-temperature ultrasonic treatment of various durations is due to the formation of a uniform defect structure. For the LSP processing technology, the mechanical properties of the hardened layer are not uniform [1,2,[10][11][12].…”
Section: Introductionmentioning
confidence: 96%
“…It was found by Yasnii et al [4] that the impact toughness of 15Kh13MF steel increases up to twofold after LSP with a power density ranging from 5 × 10 8 to 2 × 10 9 W · cm −2 . The mechanism of the increase of impact toughness is mainly from two aspects: residual stresses and dislocations in the hardened layer [1,[5][6][7][8][9]. Prefabricated residual compressive stress can improve the stress threshold of crack growth.…”
Section: Introductionmentioning
confidence: 99%